2012
DOI: 10.1016/j.bbmt.2011.12.581
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Lower-Intensity Allogeneic Transplantation in Non-Hodgkin Lymphoma after Autologous Transplantation Failure

Abstract: We studied the outcome of allogeneic transplantation after lower-intensity conditioning regimens (reduced-intensity [RIC] and non-myeloablative [NST]) in non-Hodgkin lymphoma (NHL) relapsing after autologous transplantation. Non-relapse mortality (NRM), lymphoma progression/relapse, progression-free survival (PFS) and overall survival (OS) were analyzed in 263 NHL patients. All had relapsed after a prior autologous transplant and then received allogeneic transplantation from related (n = 26) or unrelated donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
1
17
0
2
Order By: Relevance
“…For example, in a study with a similar fludarabine and cyclophosphamide conditioning backbone, >30% of chemosensitive patients with indolent lymphoma histologies relapsed after RIC allo-SCT (48). In our study, the addition of TBI at 200 cGy not only provides additional immune suppression with very low incidence of mixed-chimerism for a NMA regimen, but may actually contribute to a survival benefit as has been recently reported in a large registry study of RIC allo-SCT for NHL following ASCT failure (49). Lastly, B-cell depletion with rituximab may contribute to reduced TRM and potentially improved survival by its impact on chronic GVHD (50, 51).…”
Section: Discussionsupporting
confidence: 60%
“…For example, in a study with a similar fludarabine and cyclophosphamide conditioning backbone, >30% of chemosensitive patients with indolent lymphoma histologies relapsed after RIC allo-SCT (48). In our study, the addition of TBI at 200 cGy not only provides additional immune suppression with very low incidence of mixed-chimerism for a NMA regimen, but may actually contribute to a survival benefit as has been recently reported in a large registry study of RIC allo-SCT for NHL following ASCT failure (49). Lastly, B-cell depletion with rituximab may contribute to reduced TRM and potentially improved survival by its impact on chronic GVHD (50, 51).…”
Section: Discussionsupporting
confidence: 60%
“…Recently published, registry study showed 3 year probabilities of PFS and OS were 21% and 32%, respectively after RIC allo-SCT who had failed prior auto-SCT. 27 Despite the lower intensity of the conditioning regimens, 3 year NRM was high at 44%. This is in contrast to our series, albeit small numbers, we observed 0% 2 year NRM in patients receiving allo-SCT after failed auto-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the other hand, it was reported that the 3-year overall survival, disease-free survival, and treatment-related mortality after RIST were 32%, 21%, and 44% in 263 patients with malignant lymphoma who underwent RIST for recurrence after auto-SCT, and that poor prognostic factors included non-total body irradiation regimen, transplant in nonremission, and poor performance status at transplant. 10 In 101 patients with DLBCL who underwent allo-SCT (myeloablative conditioning regimen, n=37; RIST, n=64) for recurrence after auto-SCT, 3-year overall survival, progression-free survival, and treatment-related mortality were 54%, 42%, and 28% with no difference in outcome between pretransplant treatments. Poor prognostic factors included early relapse after auto-SCT, age 45 years or more, and transplant in nonremission.…”
Section: Discussionmentioning
confidence: 99%